PRIORITIZATION OF WATERSHEDS FOR RUNOFF RISK AND SOIL LOSS BASED ON MORPHOMETRIC CHARACTERISTICS USING COMPOUND FACTOR AND TOPSIS MODEL - Khalid Muhammad (Mesopotamia Journal of Agriculture)
This research was conducted to delineate the prioritization of watersheds for management in respect to runoff risk and soil loss, for that purpose, thirty watersheds within Sulaymaniyah Governorate/Iraq were studied using their morphometric characteristics of the linear, shape, and relief aspects. Since the watersheds were un-gauged, and no information about their hydrological behavior, the results of this study can be used as guidance for competent authorities to prepare flood mitigation and erosion control plans.  Prioritization ranks for watersheds were conducted based on computation of compound factors and on the technique for order preference by similarity to ideal solution (TOPSIS). The results showed that the regression analysis designated that the priority rank from (TOPSIS) can be predicted from the priority rank from compound factor computation with a reasonable accurateness. Results of prioritization ranks showed that the studied watersheds those that falling under the very high level of priority includes (Bariey-Gawra, Biyara, Dolishahidan, Zharawa, Sedara, Shawr, and Jogasur), the watersheds of high priority level comprised (Ashkana, Darokhan, Galal, Zwrkan, Zaroon, Darashmana, and Khaldan). In contrast, the watersheds that are classified under moderate level involves (Bardasipi, Daragurgan, Darawyan, Zardagila, Kunamasi, Dolan, and Chawtan). The watershed lies under the low level of priority encompasses (Sactan, Khrisaraw, Bardarash, Miradie, Jublakh, Sirie, Chami-Astel, Haladin, and Bakhisarw). Hence, suitable measures are required in these watersheds to control the risk of runoff and preserve the soil from erosion.